An Appraisal of Syncretism in the Practice of Religion in Nigeria - Nwosu, Patrick (Stellenbosch Theological Journal, 2022)
The mainline conservatives in Christianity always conceive syncretism as a practice which contaminates or dilutes Christian religion with elements that are incompatible with the gospel. In taking this stance, particularly in Nigeria, two basic mistakes are made. The first mistake is to identify the western culture with 'sacred tradition.' The second mistake is to assume that western culture is a universal form of culture that has become part of what Christianity is. These mistakes call for the reappraisal of the concept and practice of syncretism in addition to raising thequestion: which religion is pure without external influences? Applying analytical and historical methods the paper makes a critical appraisal of the concept of syncretism in religion and its practice in Africa with focus on Nigeria. It offers dialogue as a way forward to achieve authentic spirituality in any religion one may opt for. The paper concludes that most religions of the world are syncretic and that the wind of the spirit blows where it wills